PROFESI JURNALIS DAN KESETARAAN GENDER (ANALISIS EKSISTENSI JURNALIS PEREMPUAN PADA HARIAN TRIBUN SUMSEL - Dinda Kencana Wulan; Hamidah Hamidah; Manah Rasmanah (Jurnal Prodi Ilmu Komunikasi, 2023)
This research is entitled "Journalist Profession and Gender Equality (Analysis of the Existence of Women Journalists in the Sumsel Tribune Daily)". The aims of this research were 1) to find out the performance of female journalists in carrying out journalistic functions and 2) to find out the implementation of gender equality management and policies in the Daily South Sumatra Tribune. The method used is descriptive qualitative. Data collection techniques used in this study were observation, interviews and documentation. Based on the results of the study 1) The performance of female journalists in carrying out journalistic functions can be seen through the first few indicators, quality shows very good and maximum results. Second, quantity: prioritizing achieving maximum targets by covering 3 news stories in 1 day plus 18 news stories a week. Third, timeliness: perseverance, the alertness of journalists to be able to complete assignments on time. Fourth, effectiveness: the use of technology is very helpful and facilitates journalists in reporting news and informing news to the office. Fifth, Independence: the level of independence of employees while carrying out their duties is very good. Sixth, commitment: there is a high work commitment so as to realize excellent work quality. 2) Implementation of gender equality management and policies in the Sumsel Tribune Daily, namely by arranging planning including adequate access to technology, participation between journalists, evaluating, work control systems have given the right to evaluate work quality in a balanced way, work scheduling and work safety security, so gender equality is not closing the possibility for anyone to have the right to enjoy the results of work for the achievements that have been achieved. If the journalist's performance is good then the career path will also increase.